Some Specific Features of Abbreviations using in Medical Terminology in English and Uzbek (On the Example of Dermatovenereological Vocabulary) (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: medical terminology; semantic; abbreviation; medical concept sphere; omoacronyms; synonymy; diagnostics